Ambulatory intravenous insulin and islet cell transplantation to treat severe type III insulin hypersensitivity in a patient with type 1 diabetes mellitus. Issue 12 (30th August 2020) - Clarke, Brigette; Loudovaris, Tom; Radford, Toni; Drogemuller, Chris; Coates, Patrick Toby; Torpy, David
Abstract: Allogenic pancreatic islet cell transplantation is an appropriate treatment option to consider in the management of refractory cases of severe hypersensitivity to insulin in patients with type 1 diabetes mellitus. Abstract : Allogenic pancreatic islet cell transplantation is an appropriate treatment option to consider in the management of refractory cases of severe hypersensitivity to insulin in patients with type 1 diabetes mellitus.